Hydrogel composition and mechanical stiffness of 3D bioprinted cell-loaded scaffolds promote cartilage regeneration - Liu, Ge; Wei, Xiaowei; Li, Junlei; Zhai, Yun; Zhang, Jingrun; Jin, Ming; Guan, Tianmin; Zhao, Dewei (Frontiers in Materials, 2024)
ObjectiveTo investigate the impact of different component ratios and mechanical stiffness of the gelatin-sodium alginate composite hydrogel scaffold, fabricated through 3D bioprinting, on the viability and functionality of chondrocytes.MethodsThree different concentrations of hydrogel, designated as low, medium, and high, were prepared. The rheological properties of the hydrogel were characterized to optimize printing parameters. Subsequently, the printability and shape fidelity of the cell-loaded hydrogel scaffolds were statistically evaluated, and the chondrocyte viability was observed. Dynamic mechanical analysis was conducted to measure the modulus, thereby assessing the scaffold’s stiffness. Following a 21-day culture period, RT-PCR, histological staining, and immunostaining were employed to assess chondrocyte activity, chondrosphere aggregates formation, and cartilage matrix production.ResultsBased on rheological analysis, optimal printing temperatures for each group were determined as 27.8°C, 28.5°C, and 30°C. The optimized printing parameters could ensure the molding effect of the scaffolds on the day of printing, with the actual grid area of the scaffolds was close to the theoretical grid area. And the scaffolds exhibited good cell viability (93.24% ± 0.99%, 92.04% ± 1.49%, and 88.46% ± 1.53%). After 7 days of culture, the medium and high concentration groups showed no significant change in grid area compared to the day of printing (p > 0.05), indicating good morphological fidelity. As the hydrogel’s bicomponent ratio increased, both the storage modulus and loss modulus increased, while the loss factor remained relatively constant. The highest number of chondrocytes-formed chondrosphere aggregates in the medium concentration group was observed by light microscopy. RT-PCR results indicated significantly higher expression levels of chondrogenic genes SOX9, Agg, and Col-II in the low and medium concentration groups compared to the high concentration group (p < 0.05). Histological staining results showed that the middle concentration group formed the highest number of typical cartilage lacunae.ConclusionThe aforementioned results indicate that in 3D bioprinted cell-loaded GA-SA composite hydrogel scaffolds, the scaffolds with the composition ratio (10:3) and mechanical stiffness (∼155 kPa) exhibit sustained morphological fidelity, effectively preserve the hyaline phenotype of chondrocytes, and are more conducive to cartilage regeneration.